Digital Era and Network Governance in Action: Policy Implementation of Business Identification Numbers in Indonesia’s Coffee Shop Sector - Sandra, Yarekha; Yusran, Rahmadani (Al-Qalam Institue, 2025)
This study explores the implementation of Indonesia’s Business Identification Number (Nomor Induk Berusaha/NIB) policy within the coffee shop sector of Padang City through the dual lenses of Digital Era Governance and Network Governance. As Indonesia advances its digital business licensing via the Online Single Submission – Risk Based Approach (OSS-RBA) system, micro and small enterprises face both opportunities and adaptation challenges. Using a qualitative descriptive method, this research draws on interviews, observations, and document analysis involving coffee shop owners, community members, and officials from the Padang City Investment and One-Stop Integrated Service Agency (DPMPTSP). The findings indicate that NIB policy effectiveness hinges on the interplay between digital efficiency and local network dynamics. While the OSS system enhances procedural speed and transparency, gaps in digital literacy and technical support hinder inclusivity. At the same time, collaborative engagement among local governments, coffee communities, and business actors has fostered informal mentoring and policy learning. The study concludes that the NIB implementation in Padang City embodies a hybrid model of digital–collaborative governance, emphasizing that successful digital transformation in public policy depends not only on technological innovation but also on trust-building and inter-actor cooperation.